Polymer Mixed Matrix Membrane with Biosynthesized Zinc Oxide/Silver Oxide Additive for Antibacterial Performance - Azhar, Faiz Hafeez; Zulkiplie, Amer Zakwan; Harun, Zawati; Raja Ahmad, Raja Adibah; Rasli, Nurul Izwanie (Emerging Advances in Integrated Technology, 2025)
Membrane technology has emerged as one of the most effective approaches for water purification, utilizing pore separation to achieve filtration without the complexities and high energy consumption associated with the traditional methods. Recent advancements have focused on modifying polymeric membranes, particularly polysulfone (PSf), by incorporating inorganic additives such as zinc oxide (ZnO) and silver oxide (AgO) nanoparticles. Thus, in this study, polymer MMMs were fabricated by incorporating biosynthesized ZnO/AgO synthesized from tea leaf extract as a reducing agent with the aim of enhancing membrane characteristics and antibacterial properties. The results showed that the antibacterial properties were enhanced by the addition of additives, particularly at higher concentrations of ZnO along with the presence of AgO. Other characteristics such as morphology, surface roughness, porosity, and hydrophilicity also produced the same increasing trend. These results proved that the addition of additives was able to enhance MMMs capabilities especially in terms of antibacterial properties.